Description and life cycle of a new species of the genus Arachnanthus (Cnidaria: Anthozoa: Ceriantharia) from the Southwestern Atlantic Ocean - Lopes, Celine S. S. [UNESP]; Scarabino, Fabrizio; Carranza, Alvar; Munoz, Ricardo Gonzalez; Morandini, Andre C.; Nagata, Renato Mitsuo; Stampar, Sergio Nascimento [UNESP] (Peerj Inc, 2023)
Background. Ceriantharia is a subclass of the phylum Cnidaria, which comprises tubedwelling marine invertebrates. This subclass is composed of three families, including Arachnactidae, with two known genera. Currently, the genus Arachnanthus has five valid species recorded from Australia, the Mediterranean Sea and both the Southern and Northern Pacific Ocean. However, at the moment, there is no record of organisms of this family from the South Atlantic Ocean. Besides that, the life cycle of any species of the genus Arachnanthus is known. The present study describes a new species of the genus Arachnanthus and its life cycle, based on specimens from Uruguay and South of Brazil. Methods. Larvae were collected by plankton net in Rio Grande-Brazil and the development and external morphology of these specimens were observed in the laboratory during two years, and subsequently described. Additionally, nine adult ceriantharians correspondent to the larvae from Rio Grande were collected in Uruguay and their external and internal anatomies, and cnidome were described. Results. Arachnanthus errans sp. nov. exhibited a free-swimming, short-lived cerinula larvae that spent short-time on the plankton. The larva developed into small and translucent polyps with a short actinopharynx, one pair of mesenteries attached to a siphonoglyph, and a medium first pair of metamesenteries. Further, the adult polyp displayed an unprecedented locomotion behavior in Ceriantharia that is first reported here, it can crawl under and in between the sediment.
Keywords: Tube-dwelling anemones; Taxonomy; Evolution; Life cycle; Temperate South America